Long‐Term Thermohaline Variations in the North Pacific Subtropical Gyre From a Repeat Hydrographic Section Along 165°E. Issue 1 (14th January 2020) - Kawakami, Yuma; Kitamura, Yoshiteru; Nakano, Toshiya; Sugimoto, Shusaku
Abstract: Long‐term thermohaline variability in the North Pacific subtropical gyre for 1996–2018 was investigated by repeat hydrography along 165°E conducted by the Japan Meteorological Agency. Potential temperature ( θ ) and salinity ( S ) in North Pacific Tropical Water (NPTW), characterized by the salinity maximum, exhibit an interannual or longer‐timescale variation with significant warming and salinification. The θ – S of NPTW originates from mixed layer temperature (MLT) and salinity (MLS) in the isopycnal outcrop region. In the NPTW formation region, the MLS determines surface density and controls the meridional position of the outcrop region. High (low) MLS and the associated southward (northward) migration of the outcrop region increase (decrease) θ – S anomalies in NPTW. The θ – S in the main thermocline/halocline associated with subtropical mode water (STMW) shows a decadal‐scale variation, with a significant cooling and freshening. These properties also derive from MLT and MLS in the isopycnal outcrop region. In the central North Pacific, including the eastern part of the STMW formation region, the MLT controls meridional migration of the outcrop region; during high (low) MLT, the outcrop region migrates northward (southward), and cold and fresh (warm and salty) STMW is formed. The signals are passed into the main thermocline/halocline through subduction of STMW. Consideration of the mechanism that generates θ – S anomalies via migration of the outcrop regions leads us to suggest surface warming and salinification in the subtropical gyre associated with global warming cause a cooling and freshening in the main thermocline/halocline and warming and salinification in NPTW, respectively. Plain Language Summary: Thermohaline (potential temperature ( θ ) and salinity ( S )) changes and variations in the upper ocean are essential elements of climate variability. Monitoring and understanding of the ocean variability are necessary to predict the coming climate changes and adapt to them. We examine the long‐term thermohaline changes and variations in subsurface layers of the North Pacific subtropical gyre using shipboard observations along a section at 165°E. Significant warming and salinification in North Pacific Tropical Water, which is the saltiest water in the North Pacific, and a cooling and freshening in the main thermocline/halocline are detected. In addition, in those regions, θ and S fluctuate on an interannual to decadal timescale. The thermohaline variations in the subsurface layers originate in the surface mixed layer in the central part of the North Pacific. The θ – S anomalies that form in the mixed layer are transported into the subsurface ocean and circulate in the anticyclonic North Pacific subtropical gyre along isopycnal (i.e., isentropic) surfaces. Furthermore, through this subduction process, large‐scale long‐term changes at the ocean surface associated with global warming, such as warming and salinification in the North Pacific subtropical gyre, can change the thermohaline structure in the subsurface ocean. Key Points: Long‐term changes and variations are observed in the salinity maximum (North Pacific Tropical Water) and the main thermocline/halocline Mixed layer salinity in the central part of the subtropical gyre controls thermohaline properties in North Pacific Tropical Water Mixed layer temperature in the central North Pacific controls thermohaline properties in the main thermocline/halocline